Poverty and Hunger in India: What is Needed to Eliminate Them - Arvind Virmani (Planning Commission Government of India, 2006)
The paper by Arvind Virmani for India’s Planning Commission examines poverty, hunger, and income distribution, challenging misconceptions that economic growth or globalization have failed the poor. Using national data, it shows gradual improvement in rural income distribution from 1972 to 2000, declining poverty rates, and a significant reduction in hunger—from 15.7% of households in 1983 to 2.1% in 1999–2000. India’s poverty and inequality levels are comparable to or better than countries with similar income levels. Despite economic progress, social indicators such as literacy and health lag due to governance inefficiencies. Virmani proposes targeted solutions, including smart card-based direct transfers to the poor, to streamline subsidies and ensure basic needs are met. The paper concludes that, with improved governance and strategic resource allocation, poverty and hunger in India can be effectively eradicated, paving the way for a more equitable society.
Planning Commission Government of India February, 2006
Keywords: Poverty Eradication; Hunger Reduction; Income Distribution; Economic Growth; Globalization; Rural Consumption; Social Indicators; Governance Failures; Public Distribution System; Smart Card Transfers; Poverty Trends; India